CLOSING GAPS IN BASIC INFRASTRUCTURE SERVICES AS AN ACTIVE PART OF NATIONAL DEFENSE - Gomez Sanchez Soto, Ruben (2023)
A large part of Peruvian society does not consider National Security and Defense important; Therefore, it is important to reflect on its interrelation with the development of the country, territorial integrity, achieving dominance and facilitating the management of the national territory. Under current conditions, the basic strategies that form the National Defense present a significant lag. The proposal for "Closing Gaps in Basic Infrastructure Services, as an active part of National Defense", is key, in order to mitigate a range of risks that are generated in Border Areas; such as population, education, health, poverty, migration, low population density, abandonment of territories, drugs and much more; that is, a very important range of problems, which add up and make the expected solutions more complex. According to the investigation carried out, the existence of a relationship between National Security and Defense with the Quality of Life of the borders has been raised, and with the urgent need to close gaps in the Border Zones. These critical needs, in remote areas, will require a major investment plan in air transport infrastructure; Therefore, the adoption of Government-to-Government Contracts is recommended. Finally, it is necessary that all those involved, public and private, can assume roles, since being far from the border areas will generate a series of risks that justify the implementation of adequate and timely governance actions, focused on recovering said areas and generate the integration of border towns.